Challenging serve myths in doubles tennis - Martínez-Gallego, R.; Salvador, S. M.; Luján, J. F. G.; Reid, M.; Ramón-Llin, J.; Crespo, M. (International Journal of Sports Science & Coaching, 2021)
Doubles tennis has received little interest from quantitative research to date. Coach-led anecdotes therefore abound. The aims of this study were therefore to evaluate the veracity of the following common anecdotes: (a) serving teams have an advantage regardless of the length of the point; (b) serving teams have a greater advantage with new balls; (c) regular teams perform better when serving than new teams and (d) serving teams decrease their performance during break points. Data from doubles hard-court and clay-court tennis were collated for 52 doubles teams during 2018 ATP tournaments. Results revealed that the advantage of serving teams was evident on the points lasting up to 4 shots. Serving teams only had a greater advantage with new balls when playing on clay courts and suffered reduced winning probabilities on break points. A team`s familiarity only seemed to positively influence outcomes on hard courts. In sum, our novel findings highlight the important role that quantitative analysis can play in challenging doubles convention and shaping contemporary practice design and match strategy.